Triply Periodic Minimal Surface-Based Heat Exchanger as Metal Hydride Hydrogen Storage Reactor - Luthfan Adhy Lesmana (AIDIC Servizi S.r.l., 2021)
Sustainable energy production growth tends to move toward hydrogen as energy carrier. Metal hydride (MH) has been considered as a promising technology to store hydrogen effectively due to relatively low-pressure working condition and high energy density, unlike compressed and liquid hydrogen. Heat exchanger (HE) that is required to manage and provide the heat during hydrogen adsorption and desorption influences the performance of the MH reactor. Recently, due to significant advancements in manufacturing technology, triply periodic minimal surface heat exchanger (TPMS-HE) has been developed in order to enhance the heat transfer and improve the cycle efficiency. In this study, TPMS-HE is implemented as the main structure of MH hydrogen storage to improve its performance, especially in terms of adsorption rate, storage capacity, and mechanical properties. Modelling and analysis using computational fluid dynamics conducted in this research is validated with experimental data. The influence of cooling conditions is studied and increase of heat transfer coefficient to 500 W/m2·K and above leads to the increase of hydrogen fraction generated per time compared to natural convection. The improvement comparison between each parameter is reported as nonlinear correlation, with forced air convection cooling condition shows as the preferable solution.